IDENTIFIKASI STRUKTUR BAWAH PERMUKAAN DI DAERAH PANASBUMI KASINAN, KOTA BATU, BERDASARKAN METODE GAYABERAT DAN SUHU - Sutasoma, Muwardi; Maryanto, Sukir; Santoso, Didik Rahadi (Department of Physics - Faculty of Science, 2014)
Study on geothermal potential in Kasinan, Batu City has been conducted based on gravity method. The aimed of this study is to determine subsurface structure in this field. Data acquisition has performed in 95 point around the location. The study was conducted to obtain Â Bouguer anomaly and residual anomaly. Upward continuation method performed to gain residual and regional anomaly values. Two types of cross-section modeling have been carried from local anomaly value : AAâ and BBâ trajectories.The depth of below surface modeling is 2000 meters. The results of modeling confirmed that the rock types compotition on AAâ and BBâ trajectory are andesite, tuff, and Lava.